Antigen presentation by Follicular Dendritic cells to cognate B cells is pivotal for Generalised Modules for Membrane Antigens (GMMA) immunogenicity. Issue 44 (19th October 2022) - Piccioli, Diego; Alfini, Renzo; Monaci, Valentina; Arato, Vanessa; Carducci, Martina; Aruta, Maria Grazia; Rossi, Omar; Necchi, Francesca; Anemona, Alessandra; Bartolini, Erika; Micoli, Francesca
Highlights: The humoral immune response elicited by GMMA is independent on the TLR2 engagement. The absence of TLR4 engagement negatively affects the anti-GMMA antibody production, but the impact on antibody functionality is dependent on the GMMA type and the presence of Alum adjuvant. The disruption of antigen presentation by FDC to cognate B cells negatively affects both antibody production and functionality when immunizing with GMMA, in absence or presence of Alum adjuvant. The immunological mechanisms of GMMA immunogenicity has been studied by using mutant mice in which the mechanisms under investigation were disrupted. Abstract: GMMA has been proposed as a potent technology platform for the design of safe, effective and affordable vaccines. As GMMA are vesicles blebbing out of the outer membrane of Gram-negative bacteria, they contain lipopolysaccharides, lipoproteins and peptidoglycans that stimulate immune cells via Toll-like Receptors 4 (TLR4) or TLR2. Being basically nanoparticles, GMMA can be efficiently captured by Follicular Dendritic Cells (FDC) for antigen presentation to cognate B cells. GMMA have shown to be highly immunogenic in preclinical and clinical studies and the engagement of TLR4 and TLR2 or antigen presentation by FDC may have a prominent role in GMMA immunogenicity, which is well worth investigating. By using GMMA derived from Shigella sonnei and Salmonella Typhimurium, we show for the first time that the antigen presentation by FDC to cognate B cells plays a major role in the induction of an effective humoral immune response upon immunization with GMMA by using both models. The engagement of TLR4 is critical to elicit an optimal antibody production, but its effect on antibody functionality is dependent on GMMA type and is dispensable when immunizing with Alum adjuvant, whereas TLR2 does not have any role for GMMA immunogenicity. Our findings represent a substantial advancement of the knowledge on GMMA mode of action and shed a light on novel perspectives for the design of safer and more effective GMMA-based vaccines. One Sentence Summary: The study demonstrated that the antigen presentation by FDC to cognate B cells plays a major role for GMMA immunogenicity.